2016
DOI: 10.1371/journal.pgen.1005937
|View full text |Cite
|
Sign up to set email alerts
|

The Promyelocytic Leukemia Zinc Finger Transcription Factor Is Critical for Human Endometrial Stromal Cell Decidualization

Abstract: Progesterone, via the progesterone receptor (PGR), is essential for endometrial stromal cell decidualization, a cellular transformation event in which stromal fibroblasts differentiate into decidual cells. Uterine decidualization supports embryo implantation and placentation as well as subsequent events, which together ensure a successful pregnancy. Accordingly, impaired decidualization results not only in implantation failure or early fetal miscarriage, but also may lead to potential adverse outcomes in all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
99
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(107 citation statements)
references
References 63 publications
8
99
0
Order By: Relevance
“…Genotyping with PCR primers: P1, P2, and P3 (Table and Supporting Information Figure S2), demonstrated absence of exon 2 in the Plzf d/d mouse (Figure a,b). Because we have previously demonstrated that Plzf protein is significantly induced in uterine tissue of ovariectomized wild type mice following injection of progesterone hormone (Kommagani et al, ), we injected ovariectomized Plzf d/d females and corresponding monogenic controls with either hormone vehicle or progesterone hormone. Western analysis clearly showed that while uterine Plzf protein is not expressed in the vehicle‐treated ovariectomized control and Plzf d/d group, Plzf protein expression is only induced in the control uterus 6 hr following progesterone administration (Figure c).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Genotyping with PCR primers: P1, P2, and P3 (Table and Supporting Information Figure S2), demonstrated absence of exon 2 in the Plzf d/d mouse (Figure a,b). Because we have previously demonstrated that Plzf protein is significantly induced in uterine tissue of ovariectomized wild type mice following injection of progesterone hormone (Kommagani et al, ), we injected ovariectomized Plzf d/d females and corresponding monogenic controls with either hormone vehicle or progesterone hormone. Western analysis clearly showed that while uterine Plzf protein is not expressed in the vehicle‐treated ovariectomized control and Plzf d/d group, Plzf protein expression is only induced in the control uterus 6 hr following progesterone administration (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…Lanes 1 and 2 represent protein isolated from the uterus of untreated and progesterone‐treated ovariectomized wild type mice, respectively. Note the significant induction of Plzf protein (75 kDa) expression (after 6‐hr) in response to progesterone administration (Kommagani et al, ). Lanes 3 and 4 represent uterine protein isolates from untreated and progesterone‐treated Plzf d/d mice, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcript levels of insulin-like growth factor binding protein-1 (IGFBP1) and prolactin (PRL) were used as markers for the decidual response in hESCs 20. hESCs were grown in DMEM media supplemented with heat-inactivated 10% FBS.…”
mentioning
confidence: 99%